Selection of Libyan Barbary Sheep - Benamer, A. R. (Al-Mukhtar Journal of Sciences, 1995)
The aim of this paper is to present a simple method of preparing a selection index for clean wool production from libyan Barbary sheep. Data on twenty five mature ewes were used to calculate the index weights. A simpl stepwise procedure for calculating index weights is prescribed & a detailed example of the calculations is given .